Hecatonquiros: Open-source hardware for aerial manipulation applications. (29th April 2020) - Perez-Jimenez, M; Ramon-Soria, P; Arrue, BC; Ollero, A
This article presents Hecatonquiros, a complete open-source ecosystem for low cost and lightweight robotic manipulators. It has been released to focus on aerial manipulation applications but can be used in any other robotic application that requires the use of manipulators. The proposed framework provides the control system, a simulation environment, and a set of back ends to allow reusing the algorithms with different hardware setups. Additionally, it is released with a set of tools to ease its usage and various examples to teach the users. Several manipulators models and end-effectors are available for the users to adapt to their different requirements. All the hardware is designed to be three-dimensional printed and its components are low cost and available in common robotic stores, so anyone can reproduce and use them. The software is available in the GitHub repositoryhttps://github.com/Bardo91/hecatonquiros .